Meningkatkan Keterampilan Berpikir Kritis dan Kolaboratif Dengan Model Pembelajaran Problem Based Learning Melalui Materi Gaya Pada Siswa Kelas IV Sekolah Dasar - Seri Ulina Keliat; Afkar Afkar; Aminah Aminah (Jurnal Ilmiah Global Education, 2026)
This research is motivated by the learning of style material in grade IV of Alur Selalas Public Elementary School which is still conventional, causing students' critical thinking and collaborative skills to not develop optimally. The purpose of this research is to analyze the effect of Problem Based Learning (PBL) on critical thinking and collaborative thinking skills, and to describe students' responses. The method used is an experiment with a One Group Pretest-Posttest Design. The research sample consisted of 20 grade IV students. Data were collected through critical thinking tests, collaborative skills observations, and student response questionnaires. The results showed that the application of the PBL model had a positive and significant effect. There was an average increase in critical thinking skills of 16.40 points (from 70.40 to 86.80). Collaborative skills also increased by 21.56 points (from 74.38 to 95.94). The increase in both skills occurred simultaneously, supported by contextual problem-solving activities in groups that stimulate analysis and collaboration. In addition, students gave a very positive response to learning with the PBL model, which was indicated by increased active involvement, conceptual understanding, a sense of togetherness, and self-confidence. Based on these findings, it can be concluded that the PBL model is effective in improving critical and collaborative thinking skills and has received a positive response from fourth-grade elementary school students on the topic of force. This model can be used as an alternative learning method to develop 21st-century competencies.